A new species of Varanus Merrem (Squamata: Varanidae) from the Pilbara region of Western Australia, with observations on sexual dimorphism in closely related species - Aplin, Kenneth P.; Fitch, Alison J.; King, Dennis J. (Zootaxa, 2006)
We describe a new species of Varanus similar to V. caudolineatus and V. gilleni but distinguishable from each of these taxa on genetic and morphological criteria. The three species are closely related and together constitute a species group within subgenus Odatria. The new species is restricted to the Pilbara region of Western Australia and appears to be sympatric with V. caudolineatus at several localities. It is more widely separated from known populations of V. gilleni. The new species is associated with mulga woodland and is at least partially arboreal, but little else is known of its ecology. Combined morphometric and meristic analyses indicate complex patterns of sexual dimorphism in all three species, including relative body elongation in females that is reflected in higher modal presacral vertebral counts in females than males of each species. Body elongation of females needs to be taken into account in future analyses of sexual dimorphism in varanid lizards.